Comparison of alcohol and fatty acid adsorption on hydrogenated DLC coatings studied by AFM and tribological tests - Simič, Rok (Strojniški vestnik, 2013)
Adsorption on hydrogenated diamond-like carbon (DLC) coatings with respect to boundary lubrication has been studied only very rarely, event hough such adsorption has proved to be one of the main boundary-lubricating mechanisms for metal contacts. For this reason, we used atomic force microscopy (AFM) and tribotests to study the ability of hexadecanol and hexadecanoic acid to adsorb onto DLC and affect the tribological properties of DLC coatings, where steel was used as a reference. We have shown that alcohols and fatty acids can adsorb onto the DLC under static conditions. However, under dynamic tribocontact conditions, although alcohol and fatty acid molecules help to decrease the wear of the coatings, they are inefficient in reducing the friction. In all the experiments the fatty acid proved to have superior adsorption abilities compared to the corresponding alcohol. Based on our results and the existing literature, tentative adsorption mechanisms that include an environmental species effect, a temperature effect and a tribochemical effect are discussed for DLC surfaces.
Keywords: adsorpcija; adsorption; AFM; alcohols; alkoholi; diamantu podobni ogljik; diamond-like carbon; DLC; fatty acid; maščobne kisline; tribologija; tribology